Transient heat stress compromises the resistance of wheat (Poales: Poaceae) seedlings to Hessian fly (Diptera: Cecidomyiidae) infestation - Currie, Yaleaka; Moch, John; Underwood, Joshua; Kharabsheh, Hamzah; Quesenberry, Amy; Miyagi, Risa; Thomas, Carolyn; Boney, Melanie; Woods, Samantha; Chen, Ming-Shun; Zhu, Lieceng (My University, 2014)
Heat stress exerts a profound impact on the resistance of plants to parasites. In this research, we investigated the impact of an acute transient heat stress on the resistance of the wheat line ‘Molly,’ which contains the R gene H13, to an avirulent Hessian fly (Mayetiola destructor (Say)) population. We found that a significant portion of Molly seedlings stressed at 40°C for 6 h during or after the initial Hessian fly larval attack became susceptible to otherwise avirulent insects, whereas unstressed control plants remained 100% resistant. Specifically, 77.8,73.3,83.3, and 46.7% of plants heat stressed at 0,6,12, and 24 h, respectively, after the initial larval attack became susceptible. Biochemical analysis revealed that heat stress caused a transient decrease in 12-oxo-phytodienoic acid, but an increase in salicylic acid accumulation in Molly plants. The change in phytohormones after heat stress and Hessian fly infestation was not observed in ‘Newton,’ a near-isogenic but Hessian fly susceptible wheat line. Instead, heat stress caused a relatively prolonged reduction in palmitoleic acid. The role of phytohormones in heat-induced loss of wheat resistance was discussed.
Keywords: Heat stress; Wheat; Hessian fly; Loss of resistance; Phytohormone